Prevalence of depression among primary caregivers of patients with cancer in Africa: a systematic review and meta-analysis study - Yilkal Abebaw Wassie; Belayneh Shetie Workneh; Enyew Getaneh Mekonen; Mohammed Seid Ali; Masresha Asmare Techane; Mulugeta Wassie; Alemneh Tadesse Kassie; Medina Abdela Ahmed; Sintayehu Simie Tsega; Agazhe Aemro; Alebachew Ferede Zegeye; Berhan Tekeba; et al. (Frontiers in Psychology)
BackgroundCancer is one of the main causes of the most extremely stressful events that can elicit emotional reactions such as depression. Cancer patient caregivers are the most involved members of the oncology team and play an important role in patient’s disease management and palliation which may adversely affect their health in the longer run, but many times the caregiver has been overlooked and ignored team. A corresponding systematic review on this topic has not yet been undertaken, even though there have been several studies about depression among primary caregivers of patients with cancer in Africa.MethodsTo find studies, we searched databases such as PubMed, Scopus, Cochrane Library, Science Direct, African Journal Online, and Google Scholar. A Microsoft Excel spreadsheet was used to extract the data, which were then transferred to STATA version 14 for analysis. The statistical heterogeneity was evaluated by using Cochran’s Q and I2 statistics. To identify publication bias, Egger regression tests and funnel plot analysis were used. Sensitivity and subgroup analyses were carried out.ResultsThe current systematic review and meta-analysis comprised all 1983 research respondents from 10 studies. The overall pooled prevalence of depression among primary caregivers of patients with cancer was 47.21% with a 95% CI (31.76, 62.65: I2 = 98.4%). According to subgroup analysis, the pooled prevalence of depression was higher in the studies that used the back depression inventory screening tool (63.95%) (95% CI: 58.76, 69.13). Additionally, we observed a high pooled prevalence of depression in existing studies conducted in Kenya (62.7%) (95% CI: 56.45, 68.95). Finally, a greater prevalence of depression was found among primary caregivers of children with cancer (64.61%) (95% CI: 58.19, 71.03).Conclusion and recommendationsThe current systematic review and meta-analysis showed that depression was prevalent among primary caregivers of patients with cancer in Africa. The study also highlighted variability in prevalence based on country, method of depression assessment, and population subgroups. Therefore, public health interventions targeting the mental health of caregivers should be promoted. Priority should be given to those who care for children.